Comparative Study of Material Removal Rate of Single-Spark And Multi-Spark Micro-EDM of Copper - Mohammad Yeakub Ali; Md Mazid Abdul; Abdus Sabur; Mohamed Rahman (International Journal of Engineering Materials and Manufacture, 2022)
Micro-electro discharge machining (micro-EDM), a noncontact material removal process, is a well-established technique for making mold cavity on any workpiece materials having a minimal electrical conductivity of 0.1 Scm-1. The spark between tool electrode (-ve) and workpiece electrode (+ve) removes materials mostly from workpiece. Knowing the time and amount of material removed in a single spark, MRR can be estimated. A number of analytical study have been reported for the estimation of MRR based on the ideal situation single-spark erosion. In case of multi-spark micro-EDM, charging and discharging do not always follow the ideal conditions of the circuit and a lot of unwanted pulses such as arching and short circuit are produced which in turn reduce the effective number of pulses per second. Moreover, in RC pulse micro-EDM, the discharges are not uniform and the current and voltage are not constant with time. As a consequence, the performances estimated based on single-spark erosion formula could be misleading in multi-spark cases. This paper presents an analytical estimation of MRR as a function of machining parameters capacitance and voltage for single spark which is then compared with the multi-spark erosion of RC pulse micro-EDM. The single spark erosion rate is estimated using the electro-thermal theories in which charging and discharging duration are derived from the RC pulse time constant and the number of sparks per unit time is counted from the single spark duration. The expression of single spark erosion volume is estimated using heat transfer equations. It is also difficult to conduct single-spark EDM experiment and it has very little practical implications. Experiments are conducted to investigate the multi-spark erosion rate. It is shown that, theoretically, the number of sparks depends on the capacitance and resistance of the circuit. However, in multi-spark erosion, it is found that the number of effective sparks depend not only the capacitance and voltages but also the conditions of micro-EDM such as the workpiece and tool materials, flushing conditions, depth of cut. It is shown that the multi-spark MRR is almost half of the calculated value which is found using the equation of single spark MRR in micro-EDM of copper. Therefore, the single spark erosion formula needs to be adjusted for each of the workpiece to incorporate with the multi-spark erosion in real conditions.